Well e^x - e^(-x) = d(e^x + e^(-x))/dx So this is set up for substitution
Let u = e^x + e^(-x) Thus du = (e^x - e^(-x)) dx
So ∫(e^x - e^-x)/(e^x + e^-x) dx = ∫du/u
= ln u + C
= ln (e^x + e^-x) + C
2006-12-20 14:46:03
·
answer #1
·
answered by Wal C 6
·
1⤊
0⤋
Oneo f the ways to solve this problem is to expand it out and solve for each term individually. What we have is a factored difference of squares: (a - b) (a + b) = a^2 - b^2. So we expand it just like that.
Integral ( [e^x]^2 - [e^(-x)]^2) dx. Whenever we have a power to a power, we multiply the exponents; therefore, we get
Integral ( [e^(2x) - e^(-2x) ]) dx
Now, these are relatively simple integrals to solve, because the inside of the function is linear. We *could* use substitution to solve it, but why?
The integral of sin(2x) is -cos(2x)/2. The integral of cos(6x) is sin(6x)/6. All we have to do is divide by the value to offset the chain rule when taking the derivative. Therefore, for
Integral ( [e^(2x) - e^(-2x) ]) dx, we get
[e^(2x)]/2 - [e^(-2x)]/(-2) + C, or
(1/2)e^(2x) + (1/2)(e^(-2x)) + C
This can be simplified further, but I think I'll stop here.
2006-12-20 19:41:09
·
answer #2
·
answered by Puggy 7
·
0⤊
0⤋
∫tanh x dx=ln cosh x
2006-12-20 14:42:44
·
answer #3
·
answered by yupchagee 7
·
0⤊
0⤋
Note that the numerator is the derivative of the denominator.
That is derivative of e^x is e^x
and derivative of e^(-x) is - e^(-x)
The integral of u' / u, where u is any funtion,
is ln( abs(u) )
Thus the ∫(e^x - e^-x)/(e^x + e^-x) dx
is ln ( /(e^x + e^-x) )
2006-12-20 14:49:22
·
answer #4
·
answered by kermit1941 2
·
0⤊
0⤋
sinh x = e^x - e^(-x)
cosh x = e^x + e^(-x)
tanh x = sinh x / cosh x
integral {tanh x dx} = ln(cosh x) + C
= ln {e^x + e^(-x)} + C
2006-12-20 14:47:28
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
wow... that looks like greek to me. MAJOR props to anyone who can figure that out... or even atempt it lol
=]
2006-12-20 14:43:49
·
answer #6
·
answered by =] 4
·
0⤊
2⤋